2007
DOI: 10.1111/j.0889-7204.2007.06483.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Implementation of Telemanagement on a Disease Management Program in an Elderly Heart Failure Cohort

Abstract: The purpose of the present investigation is to examine the impact of a telemanagement component on an outpatient disease management program in patients with heart failure (HF). A total of 282 patients in whom HF was diagnosed and who were enrolled in an outpatient HF program were included in this analysis. One hundred fifty-eight patients additionally participated in a self-directed telemanagement component. The remaining 124 patients received care at an HF clinic but declined telemanagement. During the 7-mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…Cost estimates were adjusted for cross-country purchasing power differences (PPP), using 2007 US$ PPP [30] and for inflation, using GDP prices [30] in order to make meaningful comparisons across studies. Four studies did not report the year of data collection [31][32][33][34]. For these studies the year of publication of the papers was used as reference year.…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Cost estimates were adjusted for cross-country purchasing power differences (PPP), using 2007 US$ PPP [30] and for inflation, using GDP prices [30] in order to make meaningful comparisons across studies. Four studies did not report the year of data collection [31][32][33][34]. For these studies the year of publication of the papers was used as reference year.…”
Section: Search Strategymentioning
confidence: 99%
“…Information provided was mostly limited to descriptions such as "conventional hospital-based care", "usual care", "standard care", "standardized usual care" or "usual care by physician". Eight studies reported usual care conditions in (more) detail [32][33][34][35][36][37][38][39] (Table 1). Table 1 presents the characteristics of the disease management programs included in our review.…”
Section: Usual Care Conditionsmentioning
confidence: 99%
“…Numerous evaluations have established the effectiveness of these programs in enhancing use of appropriate medications, improving functional status, reducing readmissions and mortality, and decreasing costs. [44][45][46][47][48][49][50][51][52][53][54] For example, in separate evaluations, the prevalences of appropriate vasodilator use (93% vs. 61%; P < .001), 51 b-blocker use (71% vs. 40%; P < .001), 50 and ACE inhibitor use (84% vs. 59%; P < .001) 52 were significantly greater for disease management program participants compared with nonparticipants. In addition, participation in a disease management program was associated with a 52% reduction in the risk of hospitalization for cardiovascular causes (P < .001) and a 72% reduction in ED visits (P < .01) in 1 evaluation, 45 a 36% reduction (95% CI: 16.7%-50.9%) in the risk of heart failure admission or death in another, 53 and a 67% reduction (95% CI: 41%-82%) in the adjusted risk of death in yet another evaluation.…”
Section: Transition Of Carementioning
confidence: 98%
“…[8][9][10][11][12][13][14][15][16][17][18] In 9 of these studies, readmissions were significantly lowered. These interventions included:…”
Section: Education and Assessmentmentioning
confidence: 99%
“…Patient education during hospitalization and postdischarge telemonitoring for reinforcement of education and assessment of patients 13 or postdischarge home visits and monthly calls for reinforcement, assessment, and medication compliance 8 Phone calls after discharge for patient education, assessment of symptoms and compliance, and review of medication adherence 14 Postdischarge patient education at outpatient clinics and assessment of symptoms and compliance during clinic visits 12 or during follow-up calls every 2 to 4 weeks 16 Postdischarge assessments of medication adherence, symptoms/health, and compliance through a single home visit 1 week after discharge, 18 through daily telemonitoring and outpatient clinic visits every 1 to 2 weeks, 11 and through a daily telemonitoring system. 9 …”
Section: Education and Assessmentmentioning
confidence: 99%